The effects of foot massage on restless leg syndrome in hemodialysis patients: A systematic review - Kusnendar, Kusnendar; Awaludin, Sidik (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Restless leg syndrome (RLS) is a neurological disorder that causes an irresistible desire to move the legs. RLS is a problem that is often encountered in hemodialysis (HD) patients and can affect the patient's quality of life. Purpose: To compare the effectiveness of massage therapy and aromatherapy on symptoms of restless leg syndrome and sleep quality in hemodialysis patients. Method: Systematic review study design that refers to the Preferred Reporting Items for Literature Review and Meta-Analyses (PRISMA). The literature used was published from 2013-2023 through databases including, ProQuest, Science Direct, Cochrane, Ebsco Host, SAGE Journal, Taylor & Francis, and Scopus with the keywords